Anaplastic rhabdomyosarcoma in TP53 germline mutation carriers - Hettmer, Simone; Archer, Natasha M.; Somers, Gino R.; Novokmet, Ana; Wagers, Amy J.; Diller, Lisa; Rodriguez‐Galindo, Carlos; Teot, Lisa A.; Malkin, David (Cancer, 2014)
BACKGROUND Rhabdomyosarcoma (RMS) represents a diverse category of myogenic malignancies with marked differences in molecular alterations and histology. This study examines the question if RMS predisposition due to germline TP53 mutations correlates with certain RMS histologies. METHODS The histology of RMS tumors diagnosed in 8 consecutive children with TP53 germline mutations was reviewed retrospectively. In addition, germline TP53 mutation analysis was performed in 7 children with anaplastic RMS (anRMS) and previously unknown TP53 status. RESULTS RMS tumors diagnosed in 11 TP53 germline mutation carriers all exhibited nonalveolar, anaplastic histology as evidenced by the presence of enlarged hyperchromatic nuclei with or without atypical mitotic figures. Anaplastic RMS was the first malignant diagnosis for all TP53 germline mutation carriers in this cohort, and median age at diagnosis was 40 months (mean, 40 months ± 15 months; range, 19‐67 months). The overall frequency of TP53 germline mutations was 73% (11 of 15 children) in pediatric patients with anRMS. The frequency of TP53 germline mutations in children with anRMS was 100% (5 of 5 children) for those with a family cancer history consistent with Li‐Fraumeni syndrome (LFS), and 80% (4 of 5 children) for those without an LFS cancer phenotype. CONCLUSIONS Individuals harboring germline TP53 mutations are predisposed to develop anRMS at a young age. If future studies in larger anRMS cohorts confirm the findings of this study, the current Chompret criteria for LFS should be extended to include children with anRMS irrespective of family history. Cancer 2014;120:1068–1075. © 2013 American Cancer Society. Children with germline TP53 mutations are predisposed to develop anaplastic rhabdomyosarcoma at a young age. Extension of the current Chompret criteria for Li‐Fraumeni syndrome to include children with anaplastic rhabdomyosarcoma irrespective of family history should be considered.